Peran paguyuban terhadap pertumbuhan UMKM di kawasan sentral industri tahu takwa Desa Tinalan Kota Kediri - Shiddiqah, Rahimmah; Adi, Khofifatu Rohmah (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial, 2023)
The background to this research problem is that the growth of MSMEs is still unstable, where there are constraints such as institutions, human resources, marketing, technology and capital. The aims of this study were: 1) To find out the role of the association in increasing the growth of MSMEs in the Tofu Takwa industrial central area in Tinalan Village, Kediri City; 2) Describe the results of community development in increasing the growth of MSMEs in the Tofu Takwa industrial central area in Tinalan Village, Kediri City. The method used is a qualitative approach with data collection techniques in the form of observation, interviews, documentation. The source of key informants is the association's management while the supporting informants are members of the association. The results of the study show that the efforts made in the growth of MSMEs are that the association provides 1) the role of the association in facilitating the distribution of information and handling business constraints, the role of the association in educating skills in the form of online sales and packing training, the role of the association in representational skills is the realization of tofu village tourism; 2) The result of the development of the association as a whole is the realization of culinary tourism centers in the tofu village and product innovations that continue to grow as well as more advanced community resources with training. With this association, Village Tofu Tourism has experienced significant development. Latar belakang masalah penelitian ini adalah pertumbuhan UMKM yang masih belum stabil, dimana terdapat kendala seperti kelembagaan, SDM, pemasaran, teknologi dan modal. Tujuan penelitian ini adalah: 1) Mengetahui peran paguyuban dalam meningkatkan pertumbuhan UMKM di kawasan sentral industri Tahu Takwa di Desa Tinalan Kota Kediri; 2) Mendeskripsikan hasil pengembangan paguyuban dalam meningkatkan pertumbuhan UMKM di kawasan sentral industri Tahu Takwa di Desa Tinalan Kota Kediri. Metode yang digunakan adalah pendekatan kualitatif dengan teknik pengumpulan data berupa observasi, wawancara, dokumentasi. Sumber informan kunci yaitu pengurus paguyuban sedangkan informan pendukungnya adalah anggota paguyuban. Hasil dari peran yang dilakukan paguyuban adalah bahwa paguyuban memberikan 1) Peran memfasilitasi, peran keterampilan mendidik dan peran keterampilan representasi; 2) Hasil pengembangan paguyuban secara keseluruhan adalah terwujudnya santra wisata kuliner kampung tahu dan inovasi product yang terus berkembang serta sumber daya masyarakat yang lebih maju dengan adanya pelatihan-pelatihan. Dengan adanya paguyuban ini maka Desa Wisata Kampung Tahu mengalami perkembangan yang signifikan.